The Measurement of Rock Stress for Tunnelling - I Gray (The Australasian Institute of Mining and Metallurgy, 2014)
While in some cases it is vitally important to measure the virgin stress in rock prior to tunnelling there are a number of cases where such stress measurement is really not required. The concept of having to have a number to put in a numerical model representing a continuum is often quite inappropriate. This paper discusses the cases when virgin stress measurement is required and the most appropriate means to measure it. The techniques discussed cover all of the overcoring systems, hydrofracture and borehole breakout measurements. It also covers the use of rock surface stress measurement, which is easy to perform and should be used to check for changing stress conditions. Unfortunately this technique has been ignored in recent times because engineers are addicted to numerical models requiring far field stresses rather than measuring the real values that exist where they matter – at the tunnel wall. A case is presented in which the measurement of surface stress in a tunnel boring machine tunnel enabled the far field stress to be determined in what must be the world’s largest overcore.CITATION:Gray, I, 2014. The measurement of rock stress for tunnelling, in Proceedings 15th Australasian Tunnelling Conference 2014 , pp 153–160 (The Australasian Institute of Mining and Metallurgy: Melbourne).